Upaya Pencegahan Banjir Dengan Pembuatan Biopori Sebagai Edukasi Lingkungan Dan Mitigasi Bencana - Nur El Fajri; Finie Lestari; Laelatul Khasanah; Muhammad Anwar Zein; Nadya Shafiyyah; Noor Athirah; Nurdia Jelita; Raihanul Qalbi; Sarah Lutfia Mutmainnah (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2023)
Flooding is one of the problems that occurs, the impact of flooding itself is not only on the environment but can have an impact on the surrounding community who live in the area, to overcome this problem the Biopori Absorption Hole (LRB) method is used which begins with counseling and making biopore holes in a location where flooding often occurs in Sangau village. The level of achievement obtained is how the Sangau Village Community can utilize biopores to overcome flooding problems by utilizing organic waste/waste